Exploring skills-related challenges faced by educators in the implementation of inclusive teaching and learning: A case study of the Thabo Mofutsanyana District - Makola, Solomon; Ndlovu, Mkhumbulo; Makate, Lerata Jan (Educational Challenges, 2025)
Purpose. The study aimed to explore skills-related challenges faced by educators in inclusive education environments in South Africa, focusing on the Thabo Mofutsanyana District. Methodology. Grounded on qualitative methods, data were collected through semi-structured interviews with principals, educators who are School-based Support Team (SBST) committee members, district officials who are part of the District-Based Support Team (DBST) and Chairpersons of School Governing Bodies (SGBs), alongside document analysis of policies such as the Education White Paper 6 (EWP6). Results. The findings revealed that educators encounter challenges in supporting learners with special education needs (LSEN) due to inadequate training, resources, and skills, particularly in operating gadgets like braille machines and use of sign language in communication. Discussion. Professional training workshops, co-teaching models, and Professional Learning Communities (PLCs) were identified as solutions to build educators’ capacity. These mechanisms enable collaborative learning, improve teaching strategies, and promote inclusivity by addressing diverse learner needs. Conclusion. The study concluded to underscore the importance of equipping educators with practical skills and adequate resources to create a conducive teaching and learning, inclusive classroom environment.